Validated Analytical Spectrofluorimetric Method for Quantitation of Diphenhydramine HCl in Commercial Dosage Forms - Syed Najmul Hejaz Azmi; Aisha Al-Mahroqi; Khoula Al-Mamari; Shaima Al-Shukaili (Journal of New Developments in Chemistry, 2018)
Diphenhydramine HClis a weakly fluorescent drug having tertiary amine group forming ion pair complex with eosin Y in dichloromethane at pH 5 in disodium hydrogen phosphate-citric acid buffer solution. The complex formation was the basis for the development of new analytical method for determination of active diphenhydramine in pharmaceutical formulations. The stoichiometric ratio between diphenhydramine and eosin Y was studied by mole ratio method and found to be 2:1. The ion-pair complex showed maximum fluorescence emission intensity at 554 nm with excitation at 259 nm. The linear dynamic range was obtained in the concentration range of 2-22 µg mL-1 with a linear equation of FI = 0.361 + 13.675 C. The apparent Gibb’s free energy (ΔGº) was calculated and found to be -80.783 KJ mol-1, confirmed the feasibility of the reaction. The proposed method was successfully applied to the determination of diphenhydramine HCl in pharmaceutical formulations and in good agreement with the reference method.
Keywords: diphenhydramine HCl